PD-1 inhibitor-augmented HAIC-TKI therapy in hepatocellular carcinoma with portal vein tumor thrombosis: real-world survival benefits, safety, and subgroup-specific efficacy - Cao, Fei; Wen, Chunyong; Wang, Yujia; Tan, Hongtong; Hao, Shaohuan; Chen, Jinbin; Chen, Shuanggang; Shen, Lujun; Xie, Lin; Qi, Han; Huang, Tao; Zhang, Yaojun; et al. (Frontiers in Immunology, 2025)
BackgroundPD-1/PD-L1 inhibitors have shown efficacy in improving the prognosis of patients with hepatocellular carcinoma (HCC) accompanied by portal vein tumor thrombosis (PVTT) in pivotal clinical trials including the landmark IMbrave150 study. However, not all the patients benefit from the PD-1/PD-L1 blockade immunotherapy. This study aimed to improve the identification of PVTT-associated HCC patients who may benefit from the combination of PD-1 inhibitor and hepatic arterial infusion chemotherapy (HAIC) and tyrosine kinase inhibitor (TKI) treatment under real-world conditions.MethodsFrom 377 HCC-PVTT patients receiving HAIC-TKI ± PD-1 inhibitors (2016-2023), we compared 76 dual-therapy (HT) and 175 triple-therapy (HTP) cases. Median follow-up period was 34.8 months in the HT group and 33.4 months in the HTP group (P=0.175). Propensity score matching (1:1 caliper=0.2) was used to balance baseline characteristics. Overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and safety were evaluated in both groups. Specific subgroups including Vp4 type PVTT, extrahepatic metastases, and patients over 60 years old, were analyzed.ResultsTriple therapy significantly improved median OS (24.6 vs. 13.5 months; HR=0.58, 95%CI:0.42–0.80; P=0.001) and PFS (11.1 vs. 6.4 months; HR=0.56, P<0.001), with a 15% absolute ORR increase (66.3% vs. 51.3%, P=0.034). In subgroup analysis, for patients with Vp4 type PVTT, the addition of PD-1 inhibitor prolonged overall survival by 6.0 months (P=0.04). For patients aged 60 years and above, the addition of PD-1 inhibitor prolonged overall survival by 1.9 months (P=0.363). For patients with extrahepatic metastasis, the addition of PD-1 inhibitor prolonged overall survival by 3.0 months (P=0.913). Grade 3–4 adverse events were comparable (30.9% vs. 19.7%, P=0.09), but two patients experienced immune treatment-related fatalities in the HTP group.ConclusionThe triple therapy (HAIC-TKI-PD-1) demonstrated superior efficacy over HAIC-TKI dual therapy in HCC patients with PVTT, achieving significant improvements in ORR, mOS, and mPFS, with an acceptable safety profile. However, PD-1 inhibitors showed minimal survival benefits in patients aged >60 or with extrahepatic metastases.